Evaluasi Daya Gabung Hibrida Hasil Persilangan Half Dialel Lima Genotipe Cabai (Capsicum annuum L.) di Lahan Gambut - Armaini, Armaini; Deviona, Deviona; Wardati, Wardati (Jurnal Agro Teknologi Tropika, 2015)
The objective of this study is to determine the value of general combining ability, and specific combining abilityhybrids of parental crosses by half-dialel scheme on the peat land. The experiment was carried out on the peatlandRimbo Panjang Faculty of Agriculture Riau University.The genotypes consisting of 15 crosses from IPB half dialelcrosses chili in three replicates. To analyze general combining ability (GCA) or specific combining ability (SCA)influence of the variable, analysis of variance for diallel cross according to Griffingâs method 2 was used. The resultshows, the highest value of general combining ability of stem diameter, fruit diameter, fruit weight and total weight perfruit were obtained from genotype C5. Genotype C159 has high value of general combining ability of plant height, stemdichotomous and crown width, and Genotype C 120 has high value of general combining ability of length fruit.Meanwhile the highest specific combining ability based on yield component is genotype C5xC120